2021
DOI: 10.1186/s12872-021-02044-z
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic and laboratory findings in coronary slow flow phenomenon: cross-sectional study and review

Abstract: Background Coronary sow-flow phenomenon (CSFP) is defined as slow passage of the contrast injected into the coronary arteries without distal obstruction of the vessel. Methods The present study was a cross-sectional, descriptive-analytical study performed at the Seyed-al-Shohada Heart Center during 2018–2019. The eligible patients based on the inclusion and exclusion criteria were divided into the study group showing the CSFP and the control group … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 51 publications
0
4
0
1
Order By: Relevance
“…The role of inflammation in atherosclerosis has been demonstrated in numerous studies. 24 - 26 White blood cell (WBC) count and NLR, a derivative of WBC, are markers of systemic inflammation. As a matter of fact, the findings of this study revealed that NLR is a strong and independent factor for CSF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of inflammation in atherosclerosis has been demonstrated in numerous studies. 24 - 26 White blood cell (WBC) count and NLR, a derivative of WBC, are markers of systemic inflammation. As a matter of fact, the findings of this study revealed that NLR is a strong and independent factor for CSF.…”
Section: Discussionmentioning
confidence: 99%
“…O papel da inflamação na aterosclerose foi demonstrado em numerosos estudos. [24][25][26] A contagem de glóbulos brancos (GB) e RNL, um derivado de GB, são marcadores de inflamação sistêmica. De fato, os achados deste estudo revelaram que a RNL é um fator forte e independente para o FLC.…”
Section: Discussionunclassified
“…Coronary slow phenomenon is a condition that is characterized by the slow passage of contrast in one or more coronary arteries during the angiography without the obvious obstruction of the distal vessels. 81…”
Section: Rdw and Atherosclerotic Plaque Formationmentioning
confidence: 99%
“…The occurrence and progression of CSFP may involve coronary microcirculation disorders, endothelial function impairment, inflammation, oxidative stress, atherosclerosis, and an imbalance in vasoactive substances. [2,3] In coronary arteriography, CSFP is observed in 1% to 7% of patients with chest pain, and 4% of those with unstable angina also exhibit CSFP. [4][5][6] Individuals affected by CSFP experience recurrent chest pain, frequent hospitalizations, and repeated cardiac catheterizations.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, CSFP is more prevalent in male patients, with twice as many males as females affected. [2] Consequently, most of the research participants were male, leaving a limited representation of females. Theoretically, females may exhibit distinct characteristics.…”
Section: Introductionmentioning
confidence: 99%